The Meaning of Verses on Parents-Children Relationship as Basis for Sandwich Generation Concept in Islam - Fitri Ayu Kusumaningrum (Millah: Journal of Religious Studies, 2023)
This article explores the interpretation of Quranic verses and Islamic teachings relevant to the modern concept of the sandwich generation, a demographic group simultaneously responsible for caring for aging parents and raising their own children. In the Indonesian context, where family ties and caregiving hold immense significance, understanding the intersection of Islamic principles with challenges faced by the sandwich generation is paramount. This article delves into the perspective of Indonesian scholars who analyze Quranic verses to provide insights into how Islamic teachings align with the responsibilities of the sandwich generation. Scholars’ interpretations highlight the importance of honoring parents, as commanded in the Quran, while nurturing children. They emphasize the concept of birr al-walidayn (kindness to parents), shedding light on the moral duty of children to care for aging parents, and fostering a balanced approach. Furthermore, the article discusses how Indonesian scholars emphasize the significance of self-care and seek support from the family and community. This aligns with Islamic values of moderation and collective responsibility. Scholars’ viewpoints underscore the rewards of patience and perseverance, assuring the sandwich generation that their efforts are acts of worship and have spiritual significance. Ultimately, this article provides a nuanced understanding of the sandwich generation phenomenon within the Indonesian Islamic context. It contributes to the broader discourse on family dynamics, caregiving, and the harmonization of modern challenges with timeless Islamic principles.